Komposisi Visual Dalam Membangun Dramatisasi Kekuasaan Pada Lirik Lagu Video Musik “Kamu Anggap Apa” - Sanjaya, William (Institut Bisnis dan Teknologi Indonesia, 2024)
The music video “Kamu Anggap Apa” narrates the story of a woman who is disregarded by her lover. The visual composition employed in the video effectively constructs a dramatization of power throughout its scenes. This study aims to elucidate the role of visual composition in constructing a dramatization of power within the lyrics of the song, thereby ensuring the proper conveyance of its message. The research methodology employed is qualitative, with purposive sampling employed to select research objects, specifically screenshots, as explanatory materials for the study objects. The study involves a detailed description of the song lyrics and screenshots. Subsequently, a discussion ensues on the application of visual composition in constructing a dramatization of power, which is subsequently correlated with the realization of the song’s message. The research findings reveal diverse applications of visual composition that depict power and a secure environment. These portrayals symbolize the protagonist’s success and liberation in achieving their objectives. The utilization of visual composition facilitates the effective communication of the song’s message to the audience.